How not to do it - Karl Betz (Intervention. European Journal of Economics and Economic Policies, 2011)
First paragraph: After the election in autumn 2009 the new Greek government revised the previous conservative government's budget outlook. Published debt estimates ballooned. And in their wake the interest rates on Greek government bonds went through the roof.
Keywords: 330